Association of predicted lean body mass and fat mass with prognosis in patients with heart failure preserved ejection fraction - Wen Su; Xiaopu Wang; Qian Wang; Junyu Pei; Zhenfei Fang (PLoS ONE, 2025)
Background Previous studies have shown that body composition influences the prognosis of heart failure patients; however, the prognostic value of lean body mass and fat mass in patients with heart failure with preserved ejection fraction (HFpEF) remains unclear. This study aimed to investigate the association of lean body mass index and fat mass index with the prognostic outcomes in patients with HFpEF. Methods We performed a post hoc analysis of data from the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial to assess the relationship between Lean BMI and FMI with the adverse events. The primary endpoint was defined as a composite of cardiovascular death, aborted cardiac arrest, or heart failure hospitalization. Results A total of 3,320 patients were included, with a median follow-up of 3.3 years. Among them, 624 occurred a primary endpoint event, and 503 died. Lean BMI was not associated with the primary endpoint (HR 0.98, 95% CI 0.82–1.16) but was found to reduce the risk of all-cause mortality (HR 0.74, 95% CI 0.61–0.91). In contrast, FMI was associated with an increased risk of both the primary endpoint (HR 1.29, 95% CI 1.09–1.55) and all-cause mortality (HR 1.46, 95% CI 1.19–1.79). Conclusion In patients with HFpEF, a higher FMI was strongly associated with increased risks of both the primary endpoint and all-cause mortality, while an elevated LBMI was associated with a reduced risk of mortality.